New readings in Latin American and Spanish literary and cultural studies - Martins, Laura M. (Cambridge Scholars Pub., 2014)
Presenting and interrogating a range of texts and discourses, this collection brings into focus a broad range of topics whose common denominator is the intersection between cultural productions and politics in different moments of the history of Latin America and Spain. From the struggles of class distinction, identity and community in 19th and 20th century and contemporary Latin America as explored in photography, literature and film, to how political and sexual transgressions from medieval ...